Criminalizing Homelessness: Circumstances Surrounding Criminal Trespassing and People Experiencing Homelessness - Diamond, Brie (Criminal justice policy review, 2022)
Criminal trespassing (CT) is an understudied misdemeanor offense often enforced to maintain control over contested spaces and, in practice, often disproportionately used against disenfranchised populations such as the homeless and mentally ill. This study uses the CT case files of a county criminal district attorney’s office to investigate how cases involving defendants experiencing homelessness are handled compared with other defendants. Results show that homeless defendants make up a substantial portion of all CT cases, are more likely to be repeat CT defendants, and account for most jail sentences. Whereas defendants with mental health issues were often deferred for services, this avenue was not similarly extended to homeless defendants. Qualitative analyses show varied circumstances related to CT arrest for homeless and non-homeless defendants. The findings suggest various policy implications to refocus police resources and promote interagency cooperation to address the underlying causes of CT involvement by people experiencing homelessness.